Post-Election Violence in Africa: The Case of the CEMAC Sub-Region (Czech Journal of Multidisciplinary Innovations, 2024)
Since 1990 contested elections have again become a regular fixture of the political systems of subSaharan Africa. But what do they mean? In this issue of post-election violence in Africa, we shall consider some elections within the African continent, most especially within the CEMAC Region and the lessons that can be drawn from them, both for democracy and for best electoral practice. None of these elections was ‘typical’ for the continent. All were fiercely contested. Those in Cameroon, Gabon, Chad, Central Africa Republic and the Republic of Congo. Each has something important to say about the meaning of elections in Africa and the challenges that arise in running them well. From across the continent, election-related violence has imposed itself as a full component of Africa’s political landscape in the past two decades. The prevalence of such violence in Africa has led to the production of abundant literature dedicated to the matter. This research seeks to contribute to the existing academic literature by focusing specifically on the patterns, causes and consequences of post-election-related violence within the CEMAC sub-region. The central argument of the article is that, although the patterns, causes and consequences of electionrelated violence do not necessarily follow the same trends in different African countries (due to, among other factors, inter-country historical, socio-economic and political differences), there are similarities in the types, causes and consequences of such violence on the continent. While a thorough understanding of the patterns and causes of election-related violence in Africa constitutes an important point of departure in addressing the problem, an effective prevention strategy should embrace a multi-level approach targeting all significant stakeholders in any electoral process, including the political leadership, the electoral management body, civil society organizations, the general public and external partners.